Motivation to Learn Employee Class And Regular Class In Waingapu Nursing Program of East Sumba Regency - KAHI, IMELDA RAMBU; GUNAWAN, YOSEPHINA ELIZABETH SUMARTINI; HARA, MARIA KARERI; LIUNOKAS, OKLAN BT (JURNAL KESEHATAN PRIMER, 2017)
Introduction: Learning motivation plays an important role in the learning process because the learning process requires the interaction and active participation of the learners to succeed. Method: Researchers use Descriptive research with the number of samples as many as 75 students determined by Purposive Sampling data collected using questionnaires and analyzed univariately. Results: motivation to learn students based on intrinsic motivation employee class (good interest 84%, less than 16%, discipline of both 88%, approximately 12%) and regular classes (interest either 96%, less than 4%, discipline of both 98%, less than 2%) And extrinsic motivation of employee class (good family 100%, good friend 88%, less 12%, lecturer good 100%, and environment good 96%, less 4%). Regular class (good family 98%, less 2%, good friend 98%, less 2%, lecturer good 98%, less 2%, and good environment 100%). Conclusion: Student learning motivation is divided into 2 namely intrinsic motivation and extrinsic motivation. Intrinsic motivation consists of interest and discipline whereas extrinsic motivation consists of the support of family, friends, lecturers and the environment. Both types of motivation between employee class and regular class are both in the range/category either.